2009
DOI: 10.1590/s1679-62252009000100010
|View full text |Cite
|
Sign up to set email alerts
|

Diet of four annual killifishes: an intra and interspecific comparison

Abstract: We examined the diet of 4 annual fishes, Austrolebias viarius, Austrolebias cheradophilus, Austrolebias luteoflammulatus and Cynopoecilus melanotaenia inhabiting temporal ponds of southeastern Uruguay, by analysis of stomach contents. Fishes were captured from fifty ephemeral ponds of Castillos Lagoon basin, in the region of the Humedales del Este. We identified 13099 individual prey items extracted from 669 stomachs of the four captured species. In the studied system, annual killifishes represents the most ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
78
6
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(101 citation statements)
references
References 40 publications
9
78
6
8
Order By: Relevance
“…in this study, the A. vandengerbi had an equal adult sex ratio (i.e., 1:1), but there was a slight non significant female biased ratio for N. ornatipinnis. These values were similar to Laufer et al (2009) who found a ratio of 1:1 (males:females) for Austrolebias spp. and C. melanotaenia in ephemeral ponds in Uruguay; but differed from Gonçalves et al (2011) whom observed a ratio of 2:1 for C. melanotaenia in ephemeral ponds Southern Brazil, and from Calviño (2005) who reported a sex ratio of 1:4 for N. ornatipinnis from Argentina.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…in this study, the A. vandengerbi had an equal adult sex ratio (i.e., 1:1), but there was a slight non significant female biased ratio for N. ornatipinnis. These values were similar to Laufer et al (2009) who found a ratio of 1:1 (males:females) for Austrolebias spp. and C. melanotaenia in ephemeral ponds in Uruguay; but differed from Gonçalves et al (2011) whom observed a ratio of 2:1 for C. melanotaenia in ephemeral ponds Southern Brazil, and from Calviño (2005) who reported a sex ratio of 1:4 for N. ornatipinnis from Argentina.…”
Section: Discussionsupporting
confidence: 90%
“…Males of both species exhibited a larger body size than females in regards to both standard length and body depth. This trend has been observed in other species of tropical annual rivulids including Cynopoecilus melanotaenia (Regan, 1912) and several species of Austrolebias (Laufer, Arim, Loureiro, Piñeiro-Guerra, Clavijo-Baquet & Fagúndez, 2009). These differences in body size play an important role in sexual selection (Garcia et al, 2008).…”
Section: Discussionsupporting
confidence: 62%
“…Independently of temperature effect, the higher length of males in rivulids was also observed for several species (e.g. Walford & Liu 1965, Liu et al 1975, Laufer et al 2009, Arenzon et al 2001) and is considered a pattern of Austrolebias species (Costa 2006).…”
Section: Figura 2 Crescimento De Machos (A) E Fêmeas (B) Dementioning
confidence: 76%
“…However, few biological studies have been conducted so far (Arenzon et al, 1999(Arenzon et al, , 2001Errea & Danulat, 2001;Shibatta & Rocha 2001;Shibatta & Bennemann, 2003;Laufer et al, 2009;Arim et al, 2010;Polaèik & Reichard, 2010), despite of the great diversity of the family (Costa, 2008) and the extreme vulnerability of some species (Costa, 2002b;Reis et al, 2003;Rosa & Lima, 2008). The lack of basic information on annual fishes is due, in part, by few ichthyological surveys in environments where these species are exclusively found (Rosa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…At the time they were conducted, the specimens were identified as Cynopoecilus melanotaenia (Regan, 1912), however, after a taxonomic revision made by Costa (2002) and in accordance with their geographic range, this species is now defined as Cynopoecilus multipapillatus Costa, 2002. Two recent studies focused on the diet (Laufer et al, 2009), and the relationships between food web structure and body size (Arim et al, 2010) of C. melanotaenia and three other rivulids. No previous study aimed to analyze reproductive aspects of C. melanotaenia and this study represents the first investigation about reproductive biology of this species.…”
Section: Introductionmentioning
confidence: 99%